Growth and Yield of Crop Lettuce Varieties Against Differences in ABmix Concentration with NFT Hydroponic System - Ramadhan, Ujang Akbar; Istiqlal, Muhammad Ridha Alfarabi; Miska, Mohammad Ega Elman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Rapid population growth has led to greater nutritional needs and increased market demand, but this has also been accompanied by a decline in food production due to land conversion. This study aims to analyze the impact of crop variety on the growth and yield of lettuce, as well as the impact of AB mix concentration on the growth and yield of lettuce in a Nutrient Film Technique (NFT) hydroponic system. This study employs a nested design with two variables: variety and AB mix concentration. The variables studied in this research include AB mix concentration and lettuce crop variety, each with three replications. The AB mix concentrations applied were 800 ppm, 1,000 ppm, 1,200 ppm, and 1,400 ppm. The lettuce varieties used were General, Georgia, and Kanita 19. The results showed significant differences in all parameters between lettuce varieties, except for the weight of the heads. The Georgia variety showed the best suitability at a concentration of 1,000 ppm, while the General variety was suitable at a concentration of 1,200 ppm. The Georgia variety recorded the highest results in terms of leaf count and production compared to the General and Kanita 19 varieties.